Characteristics of Oviposition, Favor, and Life Cycle Aedes Aegypti Mosquitoes on Various Types of Water In Kendari City - Nurqomaria Nurqomaria; Agus Kurniawan Putra; Cici Damayanti (Pascasarjana Universitas Sulawesi Tenggara, 2023)
Dengue hemorrhagic fever (DHF) is an endemic disease caused by a virus and transmitted by vectors, especially Ae. aegypti and Ae. albopictus. The number of cases tends to increase and is widespread in almost all regions. For this reason, it is necessary to research and study the adaptation characteristics of Ae. aegypti in various environmental conditions to suppress its growth rate. This type of research is a pure experiment with a posttest-only control group design. The research samples were eggs, larvae, pupae, and adult mosquitoes kept in the laboratory. Data analysis used univariate analysis. The results of observing the oviposition of mosquitoes with the highest percentage were mine water that had been treated with a pH of 8.4 (32.15%), with the life cycle of mosquitoes from egg to adult lasting 10–15 days, and my water that had not been treated with a pH of 8.4 (31.36%). The life cycle reached 10–15 days. And in rainwater, pH 8.2 (16.55%), the life cycle reaches 9–15 days, then in well water, pH 8.1 (13.8%), the life cycle reaches 9–15 days. In the water in the local water company, the pH is 8.1 (6.87%), the long life cycle reaches 8–11 days, and in brackish water, the pH is 7.6 (0%) and wastewater pH (0%).